2021
DOI: 10.3390/ijms22042108
|View full text |Cite
|
Sign up to set email alerts
|

Innate Receptor Activation Patterns Involving TLR and NLR Synergisms in COVID-19, ALI/ARDS and Sepsis Cytokine Storms: A Review and Model Making Novel Predictions and Therapeutic Suggestions

Abstract: Severe COVID-19 is characterized by a “cytokine storm”, the mechanism of which is not yet understood. I propose that cytokine storms result from synergistic interactions among Toll-like receptors (TLR) and nucleotide-binding oligomerization domain-like receptors (NLR) due to combined infections of SARS-CoV-2 with other microbes, mainly bacterial and fungal. This proposition is based on eight linked types of evidence and their logical connections. (1) Severe cases of COVID-19 differ from healthy controls and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 277 publications
(420 reference statements)
0
67
0
Order By: Relevance
“…The activation of TLR7/8 has been found to evoke a strong pro-inflammatory response during acute lung injury [120]. Furthermore, the binding of SARS-CoV-2 PAMPs to the extracellular domain of human TLR1, TLR4, and TLR6 seems to be crucial for COVID-19 immunopathogenesis [121,122].…”
Section: Sars-cov-2 Inflammatory Response: Role Of Tlrsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of TLR7/8 has been found to evoke a strong pro-inflammatory response during acute lung injury [120]. Furthermore, the binding of SARS-CoV-2 PAMPs to the extracellular domain of human TLR1, TLR4, and TLR6 seems to be crucial for COVID-19 immunopathogenesis [121,122].…”
Section: Sars-cov-2 Inflammatory Response: Role Of Tlrsmentioning
confidence: 99%
“…Although the host genetic background powerfully influences the requirement for TLR4-mediated signals during SARS-CoV-2 infection, TLR4 activation seems to represent one of the critical steps for host-virus general interaction [122]. It has been demonstrated that TLR4 deficiency can induce resistance to acute manifestations that accompany the viral attack, suggesting an important role of TLR4 signaling in the profuse pro-inflammatory cytokine storm [123].…”
Section: Interaction Between the Sars-cov-2 S Protein And Tlr4mentioning
confidence: 99%
“…Whereas endosomal TLR3 detects double-stranded RNA (dsRNA), TLR7 and TLR8 sense single-stranded RNA (ssRNA); RIG-I specifically recognizes 5'-triphosphate RNA; and NLRs may directly recognize viral products, leading to the formation of inflammasomes ( Biondo et al, 2019 ). RIG-I and NLRs have been comprehensively reviewed elsewhere ( Root-Bernstein, 2021 ) and will not be covered in more detail here.…”
Section: Innate Immunity In Influenza Virus Infectionmentioning
confidence: 99%
“…The TLR-4 expresses at the surface of airway epithelial cells, macrophages may recognize the (s) protein, and once the virus releases its genomic RAN material into the cytoplasm during replication. 119 The endoplasmic RNA sensors such as TLR-3, TLR-7, and TLR-8 can further recognize it; 120 this may result in the induction of both the cytokines and the chemokines. Moreover, the infected host cells produce a wide range of pro-inflammatory cytokines and chemokines that also able to recruit several inflammatory cells at the site of infection.…”
Section: Discussionmentioning
confidence: 99%